The influence of coordination on the results in sports climbing: the underlying relations - Stankovic, D.; Pavlovic, V.; Petkovic, E. (Book of Proceedings Fis Communications 2019, 2019)
The aim of the research was to determine the relations and influences of coordination on the result in sports climbing in women. The research was conducted on a sample of 11 female participants, aged 16 +/-1.55 years, participants of the Youth World Cup in Arco, Italy 2015. The research was conducted by the use of 3 variables for the estimation of coordination (the obstacle course backwards in seconds POLN, coordination with a baton KOPA and 20 steps with a baton] 20IP), and 3 variables for the estimation of the result in sports climbing (bouldering BOULDER, lead climbing . LEAD and speed climbing SPEED). Based on the obtained results we can conclude the following: There aren't statistically significant relations between sets for the estimation of coordination and the overall result in sport. However, there is a statistically significant influence of coordination on the result in lead climbing both at the multivariate and some univariate level of each variable individually. This means that the participants whose coordination is at a higher level show better results in this discipline. However, the analysis of the influence of coordination on the success in disciplines of bouldering and speed climbing did not show a statistically significant influence at the multivariate level. A general conclusion is that the development of this ability of the climbers should by no means be neglected. Keywords: coordination, bouldering, lead and speed climbing